PEMPEK LENJER ORGANOLEPTICS FERMENTED SARDENE (Sardina pilchardus) - Ade Vera Yani; Idealistuti Idealistuti; Dewi Savitri; Nico Syahputra Sebayang (Universitas Islam Negeri Ar-Raniry, 2023)
This research was conducted to determine the organoleptic of fermented sardine pempek lenjer. The research was conducted at the Laboratory of the Faculty of Agriculture, University of Muhammadiyah Palembang and the Laboratory of the Faculty of Agriculture, University of Sriwijaya Palembang from October 2021 to April 2022. The research method used a non-factorial randomized block design (RBD) with research factors consisting of 4 levels P0 (without fermentation/control) , P1 (12 hours of fermentation time), P2 (24 hours of fermentation time), P3 (36 hours of fermentation time) were repeated 5 times. The results of the F test on the organoleptic test were followed by the tukey and dunnet tests. Parameter observation is organoleptic test. The results showed organoleptic test; sense of value 4.05; aroma with the highest value 4.10; and the highest value color is 3.80.